Reinforcing the LINC complex connection to actin filaments: the role of FHOD1 in TAN line formation and nuclear movement - Antoku, Susumu; Zhu, Ruijun; Kutscheidt, Stefan; Fackler, Oliver Till; Gundersen, Gregg G. (Cell cycle, 2015)
Positioning the nucleus is critical for many cellular processes including cell division, migration and differentiation. The linker of nucleoskeleton and cytoskeleton (LINC) complex spans the inner and outer nuclear membranes and has emerged as a major factor in connecting the nucleus to the cytoskeleton for movement and positioning. Recently, we discovered that the diaphanous formin family member FHOD1 interacts with the LINC complex component nesprin-2 giant (nesprin-2G) and that this interaction plays essential roles in the formation of transmembrane actin-dependent nuclear (TAN) lines and nuclear movement during cell polarization in fibroblasts. We found that FHOD1 strengthens the connection between nesprin-2G and rearward moving dorsal actin cables by providing a second site of interaction between nesprin-2G and the actin cable. These results indicate that the LINC complex connection to the actin cytoskeleton can be enhanced by cytoplasmic factors and suggest a new model for TAN line formation. We discuss how the nesprin-2G-FHOD1 interaction may be regulated and its possible functional significance for development and disease.